(3MGTjI GdLQLGfj Ydi GdeWhd ddJaJGRGfjs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s ((3GdMSf Hf eMeO Hf eSYhO Hf eMeO GdjhYfGfi GdMSfi s)
(3ChdgG (B:s
(3bhdg hgPG aGPgH Edjg ef Gf GdTGFY ai GdMeO GdJYQja s
(3BNQgG (B:s
(3hGddg CYde HGdUhGH s
(3CJe JCdjagG SfI (B781 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B474s
Keywords: (3GdHdGZIs